Persepsi Kualitas Produk Memoderasi Content Marketing dan Flash Sale terhadap Minat Beli di Ramayana Denpasar - Putu Ayu Titha Paramita Pika; I Komang Cahya Patu Darma; Putu Dyah Permatha Korry; Putu Irma Yunita (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2026)
The increasingly intense competition in the retail industry has encouraged companies to adopt various digital marketing strategies, such as content marketing and flash sales, to attract consumers’ attention. However, these strategies are not always effective without a positive perception of product quality. This study aims to examine the moderating role of product quality perception in the relationship between content marketing and flash sales toward purchase intention at Ramayana Denpasar. This research employed a quantitative approach using Partial Least Squares Structural Equation Modeling (PLS-SEM) with 110 respondents selected through purposive sampling. The findings reveal that both content marketing and flash sales have a positive and significant effect on purchase intention. Nevertheless, product quality perception does not moderate the influence of content marketing, but it weakens the effect of flash sales on purchase intention. These results emphasize that consistent product quality is essential to ensure digital marketing strategies effectively increase consumer purchase intentions in the retail sector.